Perception of university students on virtual exchange program - Lim, Beatrice Fui Yee; Dayangku Aslinah Abd Rahim; Roslinah Mahmud; Khairul Hanim Pazim; Siti Hajar Samsu (Academic Inspired Network, 2022)
The COVID-19 pandemic saw the transformation of teaching and learning activities from physical to online. Travel restrictions around the halted mobility program that requires crossing of border. In the years following the pandemic, there is increase in virtual exchange programs. This study aims to examine the perception of university students who have participated in a virtual exchange program. A total of 445 respondents completed an online survey form after completing the virtual exchange program on 29 November 2021 via online meeting platform. Descriptive analysis is used to report the findings. The results indicate that students are highly satisfied with the virtual exchange program designed that covers language, cultural, traditions and food demonstration activities. However, respondents were concerned that communication and interaction during virtual exchange program were limited unlike in physical environment where interactions can take place more effectively. Albeit this limitation, respondents who have participated in this program is motivated to join such program again. They are also motivated to participate in physical exchange program. Virtual mobility program can be a highly effective medium to nurture global citizen with cross-cultural awareness and interest.